Clinicobiochemical Profile and Outcome of Children with Small Molecule Neurometabolic Disorders: A Tertiary Care Hospital Experience from India - Banerjee, Bidisha; Shinde, Supriya; Christopher, Rita; Acharya, Ullas (Journal of Pediatric Neurology, 2024)
Inborn Errors of Metabolism (IEM), though heterogenous, are not uncommon. Neurologic manifestations predominate. Without universal newborn screening, early diagnosis and treatment may lessen neuromorbidity. Hence, this study was done to understand small molecule neurometabolic disorders' presentation, diagnostic clues, and outcome. Small molecule neurometabolic disorder was diagnosed in 45 children (postneonatal onset) over 14 years (2008–2022) in a tertiary care hospital. Clinical and laboratory data were retrospectively analyzed. There were 26 boys and 19 girls. The median age at diagnosis was 19 months (interquartile range [IQR]: 8–38 months). The median diagnostic delay was 12 months in chronic encephalopathy (IQR: 1–24 months) and 1 month (IQR: 0.2–5.5 months) in the acute encephalopathy group (p ≤ 0.01). The presentation mode was chronic encephalopathy/myopathy in 29 (64.4%) and acute encephalopathy in 11 (24.4%). Diagnostic clues included unexplained developmental delay (n = 27, 60%), tone abnormalities (n = 26, 57.7%), movement disorder and ataxia (n = 16, 35.5%), acute encephalopathy (n = 11, 24.4%), neuroregression (n = 10, 22.2%), macrocephaly (n = 10, 22.2%), and alopecia (n = 4, 8.9%). Diagnostic/suggestive blood-spot tandem mass spectrometry (TMS) was seen in 34/38 (89.5%) children. Neuroimaging helped clinch the diagnosis in 17 (47%) children. Diagnostic categories were organic acidemias (n = 25, 55.6%), urea cycle disorders (n = 11, 24.4%), aminoacidopathies (n = 5, 11.1%), and fatty acid oxidation disorders (n = 4, 8.9%). The neurodevelopmental outcome was normal in 13 (28.8%), mild delay in 12 (26.6%), severe delay in 11 (24.4%), 3 deaths (6.6%), and 6 (13.3%) children being lost to follow-up. Overall, the outcome was favorable in 55% of cases. Unexplained developmental delay with tone abnormalities with or without movement disorders is a joint presentation of late-onset neurometabolic diseases. Neuroimaging studies and laboratory tests like blood-spot TMS help identify many small molecule disorders.
Keywords: encephalopathy; inborn errors of metabolism; neuroimage; neurometabolic; tandem mass spectrometry